Evaluation of The Liquid Medical Hazardous and Toxic Waste Management System at X Hospital Palembang - Sri Yuwati; Amin Rejo; Muhammad Faizal (Sriwijaya Journal of Environment, 2022)
Abstract: becomes an obstacle faced by most hospitals, due to the limited facilities, infrastructure, manpower and of course the very large funds required. Hospital X has implemented a liquid medical Hazardous and toxic materials waste management system at the Wastewater Treatment Plant (WWTP) using the aerobic filter method. This research aims to evaluate the liquid medical hazardous and toxic waste management system is done at hospital X Palembang whether it is in accordance with the Indonesian Minister of Health Regulation Number 7 of 2019 concerning Hospital Environmental Health. As well as providing assessments for accreditation programs. This research was conducted using interviews, field observations, laboratory tests and literature studies. Based on the research results, almost all processes in the liquid medical hazardous and toxic waste management system are in accordance with regulations. However, it needs to be corrected that the liquid waste quality test needs to be done at the beginning of the month, for analysis and follow-up if there are quality standards that do not fill the requirements. DO check has not been done for daily self-monitoring of liquid waste quality, health checks. Routine vaccinations and special training for waste management officers have not been done. Keywords: evaluation, hazardous and toxic materials, management system